(untitled) (Scientific journal of the Fergana State University, 2023)
This paper discusses the possibility of synthesizing new biologically active compounds based on ferrocene, in which ferrocene-containing compounds in the molecule exhibit strong biological activity due to the specific molecular structure of the ferrocenyl nucleus. The work on the synthesis of ferrocencarboxylic acid compounds with thiourea and its derivatives and their application in practice is described. This reaction was performed by diazotization. The liquefaction temperature of the synthesized compound was recorded on the SMP10 instrument, and the IR spectra were recorded on the Perkin Elmer Spectrum IR spectrometer. The individuality of the reaction product was examined by thin-layer chromatography and isolated using columnar chromatography. The yield of the main substance 1`-carboxyferrocenyl thiocarboxamide was 98% and the structure of the compound was studied using IR spectra. The obtained IR-spectral data were confirmed by the results of mass spectrometry.